Дослідження методів штучного інтелекту для аналізу мрт зображень при діагностуванні нейродегенеративних захворювань головного мозку - Любацький, А. В. (ХНУРЕ, 2024)
Neurodegenerative diseases pose significant challenges to both patients and healthcare providers due to their complex nature and often-subtle manifestations. Magnetic Resonance Imaging (MRI) has emerged as a vital tool for diagnosing and monitoring neurodegenerative diseases of the brain. However, the interpretation of MRI scans can be intricate and time-consuming for human experts, leading to the exploration of artificial intelligence (AI) methods to assist in the analysis and diagnosis process. These technologies can detect minute changes in the brain that may be overlooked by the human eye, facilitating earlier and more accurate diagnoses, and potentially allowing for treatment that is more effective planning.
Keywords: аналіз МРТ зображень; діагностування захворювань головного мозку; захворювання головного мозку